ANALISIS MODEL EMPIRIK DALAM MELANJUTKAN STUDI DI PERGURUAN TINGGI DI BIDANG ASURANSI - Novika, Fanny; Irwandi, Muhammad (P3M Trisakti School of Insurance (TSI), 2020)
Empirical analysis is an analysis obtained from data that has been observed by a researcher conducted through an experiment or making data on its own. One empirical analysis used is the Structural Equation Model (SEM). SEM is based on causality, where changes in one variable will change the other variables. One form of relationship patterns can be described through path analysis obtained using the SPSS application. Before the data is analyzed, test the reliability of the data with Cronbach’s Alpha. The experimental data used in this study were the analysis of the factors that cause students to continue their studies in university (economic factors, parental education and family environment) and analysis of the factors that cause students to choose to continue their studies in insurance (welfare factors after graduation and interest). On the data of continuing studies in university, the Cronbach's Alpha score is 0.804 and on the data of continuing study interest is 0.862. Both data are greater than 0.6 so it can be said that both data are reliabel. The data of continuing studies in university, which have the highest level of effect on continuing studies to tertiary education is parental education. In the interest analysis data which has a higher effect to measure interest in continuing studies in the insurance field is the level of economic welfare.